Mid-Term Clinical Outcomes and Hemodynamic Performances of Trifecta and Perimount Bioprostheses following Aortic Valve Replacement - Francesca Toto; Laura Leo; Catherine Klersy; Tiziano Torre; Thomas Theologou; Alberto Pozzoli; Elena Caporali; Stefanos Demertzis; Enrico Ferrari (Journal of Cardiovascular Development and Disease, 2023)
Aims of the Study: We evaluated the clinical outcome and the hemodynamic and freedom from structural valve degeneration of two standard aortic bioprostheses. Methods: Clinical results, echocardiographic findings and follow-up data of patients operated for isolated or combined aortic valve replacement with the Perimount or the Trifecta bioprosthesis were prospectively collected, retrospectively analysed and compared. We weighted all the analyses by the inverse of the propensity of choosing either valves. Results: Between April 2015 and December 2019, 168 consecutive patients (all comers) underwent aortic valve replacement with Trifecta (n = 86) or Perimount (n = 82) bioprostheses. Mean age was 70.8 ± 8.6 and 68.8 ± 8.6 years for the Trifecta and Perimount groups, respectively (p = 0.120). Perimount patients presented a greater body mass index (27.6 ± 4.5 vs. 26.0 ± 4.2; p = 0.022), and 23% of them suffered from angina functional class 2–3 (23.2% vs. 5.8%; p = 0.002). Mean ejection fraction was 53.7 ± 11.9% (Trifecta) and 54.5 ± 10.4% (Perimount) (p = 0.994), with mean gradients of 40.4 ± 15.9 mmHg (Trifecta) and 42.3 ± 20.6 mmHg (Perimount) (p = 0.710). Mean EuroSCORE-II was 7 ± 11% and 6 ± 9% for the Trifecta and Perimount group, respectively (p = 0.553). Trifecta patients more often underwent isolated aortic valve replacement (45.3% vs. 26.8%; p = 0.016) and annulus enlargement (10.5% vs. 2.4%; p = 0.058). All-cause mortality at 30 days was 3.5% (Trifecta) and 8.5% (Perimount), (p = 0.203) while new pacemaker implantation (1.2% vs. 2.5%; p = 0.609) and stroke rate (1.2% vs. 2.5%; p = 0.609) were similar. Acute MACCE were observed in 5% (Trifecta) and 9% (Perimount) of patients with an unweighted OR of 2.22 (95%CI 0.64–7.66; p = 0.196) and a weighted OR of 1.10 (95%CI: 0.44–2.76, p = 0.836). Cumulative survival at 24 months was 98% (95%CI: 0.91–0.99) and 96% (95%CI: 0.85–0.99) for Trifecta and Perimount groups, respectively (log-rank test; p = 0.555). The 2-year freedom from MACCE was 94% (95%CI: 0.65–0.99) for Trifecta and 96% (95%CI: 0.86–0.99) for Perimount (log-rank test; p = 0.759, HR 1.46 (95%CI: 0.13–16.48)) in the unweighted analysis (not estimable in the weighted analysis). During the follow-up (median time: 384 vs. 593 days; p = 0.0001) there were no re-operations for structural valve degeneration. Mean valve gradient at discharge was lower for Trifecta across all valve sizes (7.9 ± 3.2 vs. 12.1 ± 4.7 mmHg; p < 0.001), but the difference did not persist during follow-up (8.2 ± 3.7 mmHg for Trifecta, 8.9 ± 3.6 mmHg for Perimount; p = 0.224); Conclusions: Postoperative outcome and mid-term follow-up were similar. An early better hemodynamic performance was detected for the Trifecta valve but did not persist over time. No difference in the reoperation rate for structural valve degeneration was found.